Major Molecular Factors Related to Leishmania Pathogenicity - Al-Khalaifah, Hanan S. (Frontiers in Immunology, 2022)
Leishmaniasis is a major health problem with 600k - 1M new cases worldwide and 1 billion at risk. It involves a wide range of clinical forms ranging from self-healing cutaneous lesions to systemic diseases that are fatal if not treated, depending on the species of Leishmania. Leishmania sp. are digenetic parasites that have two different morphological stages. Leishmania parasites possess several invasive/evasive and patho-antigenic determinants that seem to have critical roles in Leishmania infection of macrophages which leads to successful intracellular parasitism in the parasitophorous vacuoles. These determinants are traditionally known as “virulence factors”, and are considered to be good targets for developing specific inhibitors to attenuate the virulence of Leishmania by gene deletions or modifications, thus causing infective, but non-pathogenic mutants for vaccination. Pathway of biosynthesis is critical for keeping the parasite viable and is important for drug designing against these parasites. These drugs are aimed to target enzymes that control these pathways. Accordingly, maintaining a low level of parasitic infection and in some cases as a weapon to eradicate the infection completely. The current paper focuses on several virulence factors as determinants of Leishmania pathogenicity.